The use of Torulaspora delbrueckii in carbonic maceration wines modulates their organoleptic properties and favours malolactic fermentation - Candela Ruiz-de-Villa; Jordi Gombau; Montse Poblet; Albert Bordons; Joan Miquel Canals; Fernando Zamora; Cristina Reguant; Nicolas Rozès (IVES Technical Reviews)
Recently, there has been growing interest in the study of non-Saccharomyces yeasts due to both the benefits they bring in the wine production process and their organoleptic properties. The use of the species Torulaspora delbrueckii in alcoholic fermentation (AF) together with Saccharomyces cerevisiae (Sc) has also been observed to have a positive effect on the performance of malolactic fermentation (MLF) (Balmaseda et al., 2023). This effect has been little studied in special winemaking, such as in carbonic maceration (CM), which consists of developing the FAL within the unpressed grape grains in an anaerobic atmosphere, thus producing very aromatic wines (Tesniere et al., 2011). The objective of this study is to investigate the oenological implications of inoculation of T. delbrueckii during the first stage of vinification by CM, in order to improve the fermentation process and the organoleptic characteristics of these wines.